2021
DOI: 10.1007/s12020-021-02663-8
|View full text |Cite
|
Sign up to set email alerts
|

What are the real rates of temporary hypoparathyroidism following thyroidectomy? It is a matter of definition: a systematic review

Abstract: Introduction Post-operative hypoparathyroidism is the most encountered complication of thyroid surgery and is classified as temporary or permanent. However, its incidence varies greatly in the literature ranging from 0.5% to 65%. This can be mainly attributed to the different definition of hypoparathyroidism used in each study and especially to the different time cutoff applied to distinguish temporary from permanent hypoparathyroidism. Methods We conducted a systematic literature search in PubMed, Scopus, Coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…Postoperative hypoparathyroidism (POH) is the most common and important complication and is associated with decreased serum parathyroid hormone (PTH) levels, hypocalcemia and hyperphosphatemia (3). The reported incidence of POH is 30%~68%, with a 6-month transit rate of 19%-38% and a lifetime rate of 0-20% (4,5). Transient hypoparathyroidism prolongs inpatient rehabilitation and increases hospital stays and treatment costs (6).…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative hypoparathyroidism (POH) is the most common and important complication and is associated with decreased serum parathyroid hormone (PTH) levels, hypocalcemia and hyperphosphatemia (3). The reported incidence of POH is 30%~68%, with a 6-month transit rate of 19%-38% and a lifetime rate of 0-20% (4,5). Transient hypoparathyroidism prolongs inpatient rehabilitation and increases hospital stays and treatment costs (6).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of hypoparathyroidism after thyroid surgery varies considerably ( 19 ). Reported incidence rates of transient hypoparathyroidism range from 5.49% to 67.69%; those for permanent hypoparathyroidism range from 0% to 20% ( 16 , 20 , 21 ). This problem is caused by a number of factors ( 22 , 23 ), one of which is that the definition of the timing of hypoparathyroidism is still being explored.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, by virtue of the variety of PH definitions, the published rate of symptomatic hypocalcaemia varies between 0.1% and 20.2%, and biochemical hypocalcaemia is reported to occur at a rate of 15–75% [ 12 , 13 , 14 , 15 , 22 ]. Despite these variations, a recent review found no difference of the incidence of PH at 6 versus 12 months (4.11% and 4.08%) [ 23 ].…”
Section: Discussionmentioning
confidence: 99%